Contribution of Foreign Direct Investment on Real Gross Domestic Product of Nepal - Bhusal, Santa Prasad (AJOIS: Academic Journal of Interdisciplinary Studies, 2024)
The objective of this article is to measure the contribution of Real Foreign Direct Investment (RFDI) on Real Gross Domestic Product (RGDP) covering the sample period of 2000 – 2021 AD, employing time-series data. The period 2000 AD was the peak policy changes of Nepal’s openness and updated data are available up to 2021AD. Co-integration analysis is introduced to capture long-run relationship, and Pairwise Engel Granger test, and Error Correction Mechanism (ECM) are for short-run relationship among variables. On the paper, RFDI contributes to RGDP; the coefficient is positive as well as significant at the 5 percent level in the short run only. In the long run, RFDI is not effective for the Nepalese RGDP growth like African country of Botswana. The research finds remittance, domestic capital and export, tourism earning, are important tools to RGDP growth for long run and these variables are positive and significant at 5 percent level. All the stability and diagnostic test of the model has no symbols of misspecification, residuals are normally distributed, homoscedasticity and no serially correlated.